Opportunities for co-developing groundwater governance in Barahathawa, Nepal - Bruns, Bryan; Khadka, Manohara; KC, Sumitra; Rauniyar, Amrita (CGIAR, 2024)
Research supported by IWMI, IFRPI, and local partners in Nepal indicates that crop-choice groundwater games, combined with participatory mapping and monitoring, crop-water budgeting, and multistakeholder processes, could improve groundwater governance.